2017
DOI: 10.1051/0004-6361/201628827
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of periodicity from Hαprofiles of Proxima Centauri

Abstract: We investigate retrieval of the stellar rotation signal for Proxima Centauri. We make use of high-resolution spectra taken with UVES and HARPS of Proxima Centauri over a 13-yr period as well as photometric observations of Proxima Centauri from ASAS and HST. We measure the Hα equivalent width and Hα index, skewness and kurtosis and introduce a method that investigates the symmetry of the line, the peak ratio, which appears to return better results than the other measurements. Our investigations return a most si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…These latter authors used photometric observations obtained with the Hubble Space Telescope (HST) and the automated sky survey ASAS (Pojmanski 1997;Pojmanski & Maciejewski 2004). A periodicity of 82.6 ± 0.1 days is also reported by Collins et al (2017) 2015) is likely an alias induced by the specific HARPS observation times, and concluded that the most significant rotation period of Proxima Cen is 82.6 ± 0.1 days.…”
Section: Rotational Modulation Of the Chromosphere And The Photospheresupporting
confidence: 63%
“…These latter authors used photometric observations obtained with the Hubble Space Telescope (HST) and the automated sky survey ASAS (Pojmanski 1997;Pojmanski & Maciejewski 2004). A periodicity of 82.6 ± 0.1 days is also reported by Collins et al (2017) 2015) is likely an alias induced by the specific HARPS observation times, and concluded that the most significant rotation period of Proxima Cen is 82.6 ± 0.1 days.…”
Section: Rotational Modulation Of the Chromosphere And The Photospheresupporting
confidence: 63%
“…The rotational period of Proxima Centauri is approximately 86 days (ref. 69), suggesting that LHS 1140 may be older than Proxima Centauri. Taken together, we suggest that LHS 1140 is likely to be greater than 5 Gyr in age.…”
Section: Rejection Of False-positive Scenariosmentioning
confidence: 99%
“…Collins et al (24) analyzed 13 years of spectroscopic and photometric observations and derived 82.1 days for the stellar rotation period of Proxima based on H activity index, in agreement with the period of 83 days calculated in (4) with Hubble Space Telescope (HST) photometry and confirmed in (17,25). Robertson et al (25) did not find anything relevant on longer timescales, likely as a consequence of the stochastic nature of the microflaring activity of Proxima, which dominates the H line emission and makes the analysis of this index very complex in the time domain, as already pointed out in (8).…”
Section: Is the Candidate Planetary Signal Actually Linked To The Stementioning
confidence: 99%